Yiqi Gubiao Pill for tuberculosis-associated obstructive pulmonary disease: protocol for a double-blind randomized controlled trial - Dai, Jin; Zhang, Yifan; Su, Jun; Yuan, Guoxiang; Li, Fengsen; Zhou, Zhian; Aziza; Ye, Chunying; Seyiti, Aznamu; Pida, Maihesebu; Zhang, Jian (Frontiers in Pharmacology, 2025)
BackgroundTuberculosis-associated obstructive pulmonary disease (TOPD), recognized as a high-morbidity respiratory condition in most countries, presents significant clinical challenges in differential diagnosis and comorbidity management, while substantially elevating all-cause mortality risk. Preclinical investigations of Yiqi Gubiao Pill (National Patent ZL201410536529.5) have demonstrated multi-target therapeutic efficacy, including cough suppression, bronchospasm alleviation, sputum expectoration facilitation, and disease progression retardation. This randomized controlled trial aims to systematically assess Yiqi Gubiao’s therapeutic and evaluate its safety.MethodsWe will implement a prospective double-blind randomized controlled trial utilizing 1:1 allocation ratio, randomly assigned to either the Yiqi Gubiao pill treatment group or placebo-controlled group. Following randomization, a standardized 12-week therapeutic protocol will be administered, during which serial pulmonary function assessments and quality of life evaluations will be conducted. Concurrently, validated Traditional Chinese Medicine (TCM) symptom scoring scales will be applied for score. Systematic safety surveillance will be performed through weekly monitoring of adverse events.DiscussionThis prospective, double-blind, randomized clinical trial will provide valuable data on the efficacy and safety of Yiqi Gubiao pill in treating TOPD. Positive results will offer a new treatment option for patients with TOPD.Clinical Trial Registration[ClinicalTrials.gov], identifier [NCT06676800]. Registered 30 October 2024, https://ClinicalTrials.gov.